III Coloquio Costarricense de Lexicografía: Presentación. - Sánchez Corrales, Víctor Manuel (2012)
The Lexicography Studies Program has organized the III Costa Rican Lexicography Coloquium to create academic spaces to debate Lexicography, Metalexicography, among other discilines.